Effects of Different Treatments on Storage Stability and Flavor Characteristics of Wheat Germ - Zihan SHAO; Xun GONG; Yu SONG; Shu TAO; Ying HONG; Chao LIU; Jiaqi ZHU; Mingchun WANG; Lei CAO; Jinxia YE; Kaixuan MA (Shipin gongye ke-ji)
In order to study the effects of different treatments on the storage stability and flavor characteristics of wheat germ, wheat germ after hot air treatment and radio frequency treatment was vacuum packed and stored at a temperature of 40 ℃ and a humidity of 65%. The changes of color difference, lipase activity, fatty acid value, peroxidation value and α-vitamin E in wheat germ during storage were monitored. Electronic nose and solid phase microextraction gas chromatography-mass spectrometry were used to determine the volatile substances in wheat germ, and principal component and orthogonal partial least square identification were performed. The results showed that both hot air drying and radio frequency heating could effectively passivate the lipase activity in wheat germ. The radio frequency treatment group had the best deactivation rates, which was up to 79.10%, and it was also 12.38% higher than hot air drying. Both hot air drying and radio frequency heating decreased the increase of fatty acid values (measured by sodium hydroxide) during the storage of wheat germ. After 28 d of storage, the fatty acid values in untreated, the hot air and the radio frequency treatment groups were increased by 889.81 mg/100 g (P<0.05), 37.30 mg/100 g (P>0.05) and 35.58 mg/100 g (P>0.05), respectively. The α-vitamin E content of wheat germ was decreased by 11.50% (P<0.05) and 1.67% (P>0.05) after hot air and radio frequency treatments, respectively. After 28 d of storage, the α-vitamin E content in the hot air and radio frequency treatment groups were reduced by 3.85% (P<0.05) and 4.09% (P<0.05), respectively. Electronic nose and gas chromatography mass spectrometry (GC-MS) data showed that there were significant differences of the volatile substances in wheat germ after different treatments. In summary, the untreated wheat germ had a higher concentration of n-hexanol volatile substances and showed a grassy flavor. On the other hand, the content of pyrazine volatile substances were in the hot air treatment group was higher showing more baking and cocoa flavor. Radio frequency treatment significantly reduced the grassy flavor and increased the flavor with fruity and sweet. In general, radio frequency treatment could improve the storage stability of wheat germ and reduce the loss of α-vitamin E. The results could provide a theoretical reference for improving storage stability of fatty raw materials of wheat germ and reducing the loss of nutrient substances.